Alternative healthy eating index may predict a reduced odd of endometriosis: results from a case-control study - Seyed Mojtaba Ghoreishy; Fatemeh Sadat Hashemi Javaheri; Sakine Ghasemisedaghat; Morvarid Noormohammadi; Ghazaleh Eslamian; Seyyedeh Neda Kazemi; Bahram Rashidkhani; Robabeh Taheripanah (BMC Women's Health)
Abstract Background Endometriosis, characterized as an inflammatory ailment, affects females during their reproductive years, leading to decreased quality of life. Despite the pivotal role of diet as a modifiable risk factor for various chronic conditions, its potential influence on endometriosis has remained inadequately explored. This research endeavor sought to scrutinize the association between dietary alternative healthy eating index, AHEI, and the likelihood of experiencing endometriosis among women in Iran. Methods Conducted as a hospital-centered case-control investigation, the study enlisted individuals diagnosed with endometriosis alongside healthy counterparts, confirmed by a gynecologist, between February and September 2021 in Tehran, Iran. The pattern of diet was assessed utilizing a validated Food Frequency Questionnaire (FFQ) encompassing 168 food items. Logistic regression models were employed to explore the potential connection between AHEI and the probability of endometriosis. Results The analysis encompassed 105 subjects with endometriosis and 208 individuals in good health. After adjustment for total calories intake (Kcal), occupation, smoking (yes/no), age at menarche (years), menstruation duration (days), regular menstruation (yes/no), physical activity (minutes per week) and familial history of endometriosis (yes/no), it was observed that those with the high adherence to the AHEI, had about 92% lower odds of endometriosis (Odds Ratio: 0.08, 95%Confidence Intervals: 0.03, 0.24; P for trend < 0.001). Conclusion The investigation illustrated a protective effect of healthy eating index and its components on developing endometriosis.